ENDOSCOPIC PICTURE OF FALLOPIAN TUBES STATE IN KAZAKHSTAN WOMEN WITH NATURAL STERILITY COMBINED WITH REPRODUCTIVE DISEASES - Sagimbekovna, Aketaeva Asem; Kenzhebekovna, Smailova Lazat; Kenzhetaevna, Kabikenova Dinara (International Journal of Research -GRANTHAALAYAH, 2017)
Determination of level of fallopian tube affect and assessment of fallopian tube state in women with natural sterility combined with reproductive diseases. The analysis of endoscopic surgery results was presented by sampling in 200 patients, of which 98 patients with natural sterility, 102 with secondary sterility. The patients with natural sterility were distributed by three groups: 1 group was made up with patients with natural sterility combined with endometriosis (n=33), 2 made up with patients with natural sterility combined with uterine fibroid (n=26), 3 are patients with natural sterility combined with chronic salpingitis. All patients have passed the standard examination. According to data of sonographic hydrotubation in 1 group the double-sided uterine tubes patency was observed in 28%(84,85+6,24), in 2 group in 20% (76,92+8,26), in 3 group 29 %(74,36+6,99) of cases. Under laparoscopic examination of fallopian tube the changes were observed in 1 group in 10% (30,30+8,00) of cases. In 2 group the changes are observed in 20 % (76,92+8,26) of cases. In 3 group the changes are observed in 32% (82,05+6,15) of cases. Hereby in view of the presence of patients with natural sterility the frequency of fallopian tube abnormality in three groups was equal from 30% to 82,05%, despite its double-sided patency 74,36% to 84,85%. Therefore the endoscopic interventions shall be performed not with the purpose of diagnosis verification but with medical purpose.